2017
DOI: 10.1039/c6ee03036j
|View full text |Cite
|
Sign up to set email alerts
|

From millimetres to metres: the critical role of current density distributions in photo-electrochemical reactor design

Abstract: 0.1×0.1 m2 tin-doped hematite photo-anodes were fabricated on titanium substrates by spray pyrolysis and deployed in a photo-electrochemical reactor for photo-assisted splitting of water into hydrogen and oxygen. Hitherto, photo-electrochemical research focussed largely on the fabrication, properties and behaviour of photo-electrodes, whereas both experimental and modelling results reported here address reactor scale-up issues of minimising inhomogeneities in spatial distributions of potentials, current densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(92 citation statements)
references
References 35 publications
4
88
0
Order By: Relevance
“…Crucially, this means the results from the previous section, particularly Figure 6, are validated and that the constant electrode flux model can be used to predict product separation. Hankin et al 14 demonstrated the critical importance of minimising current density distributions in PEC cells, and this design minimises this by virtue of its design.…”
Section: Current Density Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crucially, this means the results from the previous section, particularly Figure 6, are validated and that the constant electrode flux model can be used to predict product separation. Hankin et al 14 demonstrated the critical importance of minimising current density distributions in PEC cells, and this design minimises this by virtue of its design.…”
Section: Current Density Distributionmentioning
confidence: 99%
“…The placement of the membrane within the cell is further constrained by the compromise between reducing the average path length of ions between electrodes, minimising current density distribution and not block-ing light from being absorbed. There have been a number of novel examples in order to get round these issues such as a louvereddesign 13 or perforated photo electrode 14,15 . Another typical compromise is in the thickness of the membrane, where the energy loss due to ionic conduction is balanced against the gas crossover 16 .…”
mentioning
confidence: 99%
“…[311][312] Notably, although the electrocatalysts produced by these industrially viable fabrication techniques demonstrated excellent catalytic activities, 310,313 the photoelectrodes fabricated using them still showed poorer photoactivities than those state-of-the-art photoelectrodes using conventional lab-scale fabrication techniques. 254 reported that large size led to a significant potential drop for the same photoelectrode (Figure 39a, b). 316 All model photoelectrodes in their study with the size of 50 cm × 50 cm showed ⁓80% photocurrent density losses (Figure 39c) compared to the lab-scale ones (0.1 cm 2 ), which remains an obstacle to scaling up photoelectrodes on low conductivity substrates such as transparent conductive oxides.…”
Section: Membraneless Electrolyser-based Systemmentioning
confidence: 85%
“…247 Sn-doped hematite photoanodes on Ti foil substrates by spray pyrolysis to carry out both experimental and modelling study about reactor scale-up issues. 254 It was discovered that perforated photoelectrodes decreased ionic current path lengths and thus decreased macroscopic inhomogeneities in current density distributions compared to planar ones. In addition, by comparing a single 50 cm 2 hematite photoanode with eight 3.2 cm 2 photoanodes connected in parallel, Vilanova et al concluded that the multi-photoelectrode configuration produced a slightly higher photocurrent density as well as a higher photovoltage.…”
Section: Photoanode-photocathode Tandem Devicesmentioning
confidence: 99%
“…To distinguish demonstrator size from lab size, we follow the definition of Hankin et al. that one length of the device should be 10 cm or longer to be demonstrator size . Based on this definition, we give an overview of the PEC electrode types which have already achieved demonstrator size.…”
Section: Introductionmentioning
confidence: 99%